Fenomena Perjudian Online dalam Sudut Pandang Politik Hukum (International Forum of Researchers and Lecturers, 2025)
In this era of digitalization, there are many changes in lifestyle, shopping, traveling, communicating and interacting, all online. Ironically, even crime has metamorphosed to adapt to the era of digitalization. Various forms of cybercrime such as phishing, spam, spying and gambling. Gambling fans are now starting to shift from traditional gambling to the trend of online gambling. In fact, interest is increasing day by day. This is because it is easy to carry out online gambling activities without fear of being raided by law enforcement officers. It is difficult to eradicate online gambling operators because they are operated with servers located abroad. The social impact that emerged was felt by the community. Starting from the high divorce rate due to online gambling, family financial problems, and triggering other criminal acts such as theft, robbery due to losing gambling. Multi-sector efforts that can be carried out by government agencies include collaboration between government agencies and law enforcement officials in carrying out public awareness campaigns, monitoring illegal websites that provide online gambling services, collaborating with international partners, as well as strengthening regulations and law enforcement efforts.